Progress and Nature: the Myths in "The City and the Stars", Arthur C. Clarke's Novel - Villen, Monique (Amaltea. Revista de Mitocrítica, 2021)
In agreement with Scholes who states that science fiction authors often draw from myths in their novels, we propose to analyze The City and the Stars by Arthur C. Clarke in search of possible mythical features or mythological figures. The novel presents a post-apocalyptic universe where two opposite worlds arise: one that relies fully on science and another that moves away from technology. While he anticipates the effects of science and the technological advances of his time and imagines their social, moral and philosophical consequences, the author also tries to give answers to the timeless questions of the human person, integrating them into a transcendent and mysterious cosmic order.